THE INFLUENCE OF SILK ROAD CULTURE ON MODERN DESIGN: ARTISTIC FEATURES OF CHINESE BROCADE PATTERNS - ZHANG, F.; KROTOVA, T. (Art and Design, 2024)
Goal: this study aims to analyze the influence of Silk Road culture on the style of brocade patterns in the Tang and Ming Dynasties of China, as well as to consider the practices of using brocade motifs of ancient dynasties in modern design. Methodology: based on the research of scientific literature, this article compares and analyses the stylistic characteristics of brocade patterns: connected beads, curly grass, treasure and cloud; the analysis makes it possible to trace the process of formation and evolution of brocade patterns in the Tang Dynasty. The methods of figurative and stylistic, formal analysis, methods of systematisation, and processing of results are also involved. Results. The study pointed out that the opening of the Silk Road promoted cultural exchanges between East and West, and the prosperity of politics, economy, and culture in the Tang Dynasty promoted the diversity and development of patterns. The above-mentioned motives, through integration with foreign cultures, formed symmetrical beauty, curvilinear beauty, and symbolic characteristics of Tang Dynasty patterns. In the example of the creativity of the modern Chinese designer Chen Liwen, the transformation of the motif «Tiger Sniffs the Rose» and the image of the Chinese tiger of the Ming Dynasty period in the development of modern design products is shown. Scientific novelty. This article reveals the historical evolution of the popular brocade patterns in the Tang and Ming Dynasties of China, summarizes his unique artistic style, and provides inspiration for contemporary clothing innovation design. Practical significance. The significance of this study lies in providing historical data for the integration of ethnic cultures and demonstrating the overall characteristics and evolution process of the Tang and Ming Dynasties patterns.